Impact of Institutional Factors on Environmental Quality in European Union - Kisman, Zulfukar Aytac; Ozek, Yavuz; Bayat, Tayfur; Kirac, Ziya Kivanc (International Journal of Energy Economics and Policy, 2025)
Environmental quality deterioration due to negative externalities arising from the economic growth process can be minimized in economies with high institutional quality. This study examines the institutional factors affecting environmental quality in European Union countries in the period 2002-2022. According to the panel unit root test, regulatory quality and voice and accountability variables are stationary at level values. In the short- run, there is no causality from institutional quality determinants (Control of Corruption, Rule of Law, Regulatory Quality, Voice and Accountability) to environmental quality in all European Union countries. However, in the long-run, there is causality from institutional factors to environmental quality as a whole. According to the panel parameter estimation method sensitive to cross-sectional dependence, institutional factors have no effect on environmental quality in Bulgaria, Croatia, Estonia, France, Germany, Sweden. In Finland, Ireland and Spain, institutional factors have the highest impact on environmental quality.